Real-Time RF Multi-Dimensional Signal Switching Using Polarization-Dependent Optical Mixing - Qidi Liu; Mable P. Fok (IEEE Photonics Journal, 2020)
Real-time switching of RF signal properties, including phase, frequency, and amplitude, is essential for emerging high-speed RF systems to improve security, signal fidelity, and enhance data capacity. While it is easy to switch the amplitude of an RF signal at GHz speed, unfortunately, it is extremely challenging to perform phase or frequency switching of an RF signal with a fast switching time in the picosecond range. In this paper, a real-time RF signal switching technique is proposed and demonstrated based on polarization dependent four-wave mixing in a highly-nonlinear optical fiber. Due to the amplitude, phase, and frequency transparent property of four-wave mixing, the proposed scheme is capable of manipulating multidimensional RF signal of over tens of GHz frequency, and achieve frequency hopping and phase switching of a GHz RF signal. The switching time is not limited by the proposed temporal switching technique; instead, it is solely depending on the rise/fall time of the control signal itself. Furthermore, the generation of frequency hopping signal with a switching time of 50 ps, as well as simultaneously frequency and phase switching of a GHz RF signal have been experimentally demonstrated based on the proposed RF signal switching scheme.